Short, terminally modified 2′-OMe RNAs as inhibitors of microRNA - Blechinger, Jenny; Pieper, Hanna; Marzenell, Paul; Kovbasyuk, Larisa; Serva, Andrius; Starkuviene-Erfle, Vytaute; Erfle, Holger; Mokhir, Andriy (Chemical communications, 2013)
We applied 14-mer 2′-OMe RNAs as inhibitors of selected micro RNAs. To improve their properties, we introduced a trimethoxystilbene residue at the 5′-terminus and three 2′-fluoro-2′-deoxynucleotides at the 3′-terminus to obtain potent inhibitors, whose mismatch discrimination is substantially better than that of typically applied >18-mers.